Леонид Прозоров: Альбом / Прозоров Л.А. - Прозоров Леонид Алексеевич (Удмуртия, 2023)
Экземпляры: К. Х. (20240220) / Инвентарный номер: 50226 / Цена: 410.00 / Сис.шифр: 85.143(2Рос.Удм) / Авт.знак: П 78 / ГРНТИ: 18 / ББК: 85.143(2Рос.Удм)